Write source 2000 : a guide to writing, thinking, and learning - Sebranek, Patrick; Kemper, Dave.; Meyer, Verne (Wilmington, MA : Write Source/Great Source Education Group, 1999)
Presents a comprehensive writing handbook that offers the basic elements of writing, revising, and editing, forms of writing such as journaling, short stories and poetry, summaries and research papers, and provides instruction in grammar, language, and sentence structure.
Includes index.
Young Adult
Keywords: Authorship; Creative writing; English language -- Composition and exercises; English language -- Grammar; Authorship; Creative writing; English language -- Composition and exercises; English language -- Grammar